2022
DOI: 10.3390/brainsci12020206
|View full text |Cite
|
Sign up to set email alerts
|

Using Inhibitory DREADDs to Silence LC Neurons in Monkeys

Abstract: Understanding the role of the noradrenergic nucleus locus coeruleus (LC) in cognition and behavior is critical: It is involved in several key behavioral functions such as stress and vigilance, as well as in cognitive processes such as attention and decision making. In recent years, the development of viral tools has provided a clear insight into numerous aspects of brain functions in rodents. However, given the specificity of primate brains and the key benefit of monkey research for translational applications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is important to note that previous chemogenetic studies in macaques, including our own, were not able to determine if the recorded neurons are those that have expressed DREADD receptors, or if they are simply communicating with DREADD- expressing neurons. Only three recent studies in macaques have recorded spiking activity from neurons after DREADD transfection in the target region (Deffains et al, 2021; Hasegawa et al, 2022; Perez et al, 2022), and all observed a decrease in firing rate after chemogenetic inhibition of the target. However, none of these studies recorded from the amygdala, or targeted fronto-limbic circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that previous chemogenetic studies in macaques, including our own, were not able to determine if the recorded neurons are those that have expressed DREADD receptors, or if they are simply communicating with DREADD- expressing neurons. Only three recent studies in macaques have recorded spiking activity from neurons after DREADD transfection in the target region (Deffains et al, 2021; Hasegawa et al, 2022; Perez et al, 2022), and all observed a decrease in firing rate after chemogenetic inhibition of the target. However, none of these studies recorded from the amygdala, or targeted fronto-limbic circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, hM4Di has been used to selectively block the motor cortex-propriospinal neurons (PNs) pathway and affect hand dexterity [ 100 ]; to disrupt the connection between the lateral prefrontal cortex (lPFC) and the striatum involved in inhibitory control [ 101 ]; to silence the dorsolateral prefrontal cortex (dlPFC)-lateral mediodorsal thalamus (MDL) or dlPFC-dorsal caudate nucleus (dCD) pathways involved in decision-making and working memory [ 102 ]; to inactivate the rostromedial caudate (rmCD) and PFC through the positron emission tomography (PET)-guided systemic administration of CNO [ 103 , 104 ]. It has also been used to silence the PFC and induce spatial working memory deficits [ 105 , 106 ]; and to reversibly inactivate the locus coeruleus (LC) and affect cognitive functions [ 107 ]. hM4Di, equipped with Cre-dependent viral tools, provides a powerful pharmacogenetic tool to selectively inactivate neuronal circuits.…”
Section: Genetic Tools Used For Neuronal Activity Manipulationmentioning
confidence: 99%
“…In the field of fundamental or translational neurosciences, French teams work on aspects very specific to primates such as motor skills of the upper limbs (pointing, prehension, etc. ), eye movements, general motor control and basal ganglia, development and anatomy of the cortex ( Markov et al, 2013 ; Dehay et al, 2015 ; Dehay and Kennedy, 2020 ), sensory, multi-sensory and attentional processes ( Astrand et al, 2016 ; Perez et al, 2022 ), memory and executive functions ( Stoll et al, 2016 ; Wirth et al, 2017 ; Baraduc et al, 2019 ), and social cognition. Many of these teams work with nonhuman primate models in direct connection with the study of the human brain, for fundamental knowledge, for the development of new therapies and neuroprosthetics, and using models of pathologies and imaging for anatomical studies, cerebral metabolism and the search for peripheral biomarkers.…”
Section: Biosimia Network Goals and Sciencementioning
confidence: 99%